1989
DOI: 10.2307/3899500
|View full text |Cite
|
Sign up to set email alerts
|

Rooting Characteristics of Four Intermountain Meadow Community Types

Abstract: Healthy meadow communities generally hive excellent soil binding properties. However, belowground characteristics of these communities have seldom been evaluated. In 4 meadow community types (CTs) we measured root mass and root length density (RLD) at 19-cm intervals to 40 cm soil depth. The CTs occurred along a wet to dry soil moisture gradient. The ranking of CTs from wettest to driest was: Carex rubrawer& (CANE) > Juncus balticus (JUBA) > Cmex dougWi (CADO) > Poa rtenz&d (PONE). Total RLD and mass to 40 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 19 publications
6
47
0
Order By: Relevance
“…In the period of our study, however, there were no significant grazing effects on RLD. Our results confirm the findings of Manning et al (1989) and Dwire et al (2004) that meadow communities have very high RLDs (root biomass), which may explain the relatively low levels of available nutrients and high organic matter content of the riparian soil we studied.…”
Section: à2supporting
confidence: 91%
“…In the period of our study, however, there were no significant grazing effects on RLD. Our results confirm the findings of Manning et al (1989) and Dwire et al (2004) that meadow communities have very high RLDs (root biomass), which may explain the relatively low levels of available nutrients and high organic matter content of the riparian soil we studied.…”
Section: à2supporting
confidence: 91%
“…Manning (1989) found that Carex nebracensis communities had a root mass of 3,382 g/m 2 and a root length density of 95.6 cm/cm 3 compared to Poa nevadensis which had a root mass of 555 g/m 2 and a root length density of 8. cohesion and strength of stream banks through root reinforcement of bank substrates (Micheli and Kirchner, 2002). These soil binding qualities have direct applications to stream bank restoration techniques.…”
Section: Introductionmentioning
confidence: 93%
“…Plants thrive in different microsites, uptake/process nutrients, mitigate pollutants, and trap sediment (figures 2, 3, and 4). Many riparian plant species have evolved to withstand the tremendous forces of flood discharge (figures 2, 3, and 4) (Swanson 1996;Corenblit et al 2011) with their extensive root systems (Manning et al 1989;Winward 2000;Corenblit et al 2007). For riparian recovery, at least some stabilizing species must be present.…”
Section: -Riparian Area Is Expanding or Has Achieved Potential Extentmentioning
confidence: 99%